PENGARUH MODEL PEMBELAJARAN STAD DAN NHT TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Rahayu, Sri (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2015)
This research was motivated by a change of the curriculum from the curriculum KTSP is changed into the 2013curriculum which aims to make the 2013 curriculum students productive, innovative and effective. In order for a teacher-centered learning into an interactive learning. Therefore, the necessary learning model that can support the passage of the curriculum in 2013 that STAD cooperative learning model and cooperative learning model NHT. Formulation of the problem in this research is "Are there any differences in mathematics learning outcomes matrix material between students taught using cooperative learning model Student Teams Achievement Divisions (STAD) and cooperative learning model Numbered Heads Together (NHT) in class X AK of SMK Mahardika Surabaya ? ". The purpose of this study was to determine whether there is a difference in the mathematics learning outcomes matrix material between students taught using cooperative learning model Student Teams Achievement Divisions (STAD) and cooperative learning model Numbered Heads Together (NHT) in class X AK SMK Mahardika Surabaya?. The population in this study were all students of class X AK SMK Mahardika Surabaya. While the sample is composed of two classes, namely class X AK AK AK-1 and X-2. Data was collected by providing a subjective test on the subject of the matrix given to both classes. From the data analysis calculated that t_hit > t_tabel of 4.2> 1.99125 and the average value of students who use cooperative learning model STAD is greater than the average value of students who use cooperative learning model NHT. So it can be concluded that there are differences in mathematics learning outcomes in the matrix material between students taught using cooperative learning model Student Teams Achievement Divisions (STAD) and cooperative learning model Numbered Heads Together (NHT) in class X AK SMK of Mahardika Surabaya. Keywords: Model STAD cooperative learning, cooperative learning model NHT, student learning outcomes..